Teaching English for Academic Purposes (EAP) for Adults Learners Using Authentic Materials: Learners’ Perspective in English for Staff Class - Gufron (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The researcher conducted this research in an English class for staff, where the students were lecturers at a private university in Jakarta. The main objective of this study is to explore students' views on teaching English for Academic Purposes using Authentic Materials. The researcher used a quantitative research by administering a questionnaire after teaching for 15 weeks. The researcher applied a frequency test to identify students' responses in the questionnaire and analyzed them using SPPS. The results of data analysis showed that teaching English for Academic Purposes using authentic materials is more interesting than previous experiences of learning English using teaching materials that are not in accordance with students' subject matter. Besides that, using authentic materials also triggers students to be more active in speaking because they like the topics being discussed, which is related to students' real life. Students' interest in reading also increased because students were familiar with the vocabulary related to their scientific discipline. However, this method is not compatible to be implemented in a class where the students consist of various majors.